DEVELOPMENT OF THE AGRICULTURAL SECTOR AS AN EFFORT TO STRENGTHEN REGIONAL COMPETITIVENESS - Silvia Rahayu; Dorris Yadewani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to determine How the Analysis of Agricultural Sector Development to Strengthen Regional Competitiveness in Tebo Regency. This study was conducted for 1 month. The data used in this study are secondary data obtained from the BPS Bungo Regency and BPS Jambi Province websites. The data obtained were analyzed descriptively quantitatively and descriptively qualitatively. The analysis tools used are Location Question (LQ) and Shiftshare Analysis. Based on the results of the study, it was found that the leading economic sectors in Tebo Regency are the Government Administration, Defense and Compulsory Social Security, Agriculture, Forestry and Fisheries, Other Services, Real Estate, Electricity and Gas Procurement and the Information and Communication sector. The agriculture, forestry and fisheries sector is the second leading sector in Tebo Regency with an average LQ value of 1.91 (> 1). This can also be proven through the agricultural sector in the economic structure of Tebo Regency playing a fairly large role. The results of the shift share calculation for the agriculture, forestry and fisheries sector show that it has a proportional (+) and differential (+) shift value, meaning that the sector has experienced significant growth both in Jambi Province and Tebo Regency, which means that the agriculture, forestry and fisheries sector of Tebo Regency is able to compete with similar products in other regencies and cities.